Tratamento conjugado de lixiviado com esgotos domésticos em reator uasb - Ramos, Patrícia Carvalho de Aquino (2009)
In terms of the actual Brazilian scenario, 56% of the solid s treatment units produce leachate, 46.8% of this leachate is treated and 70.4% of Brazilian residences are sewered. The development of methods to jointly treat landfill leachate and domestic sewage must recognize the great potential that landfill leachate has as a pollutant and the advantages gained by this combined treatment. The combined treatment of leachate and domestic sewage already exists at full-scale but studies on the optimum levels of dilution of the leachate with sewage are yet to be resolved. The objective of this work was to study the efficiency of a UASB reactor treating landfill leachate in combination with different proportions of domestic sewage, evaluate the influence of the organic loading on the treatment process and develop a biological treatment technology for residual liquids with high pollution loads. The study was carried out between February 2008 and February 2009. The UASB reactor was constructed, installed and monitored at EXTRABES in the municipality of Campina Grande PB. The UASB was constructed in PVC tubing with a diameter of 150mm, 2.35m in height and with a total volume of 41.5L and the treatment consisted of two phases. In the first phase of operation, the UASB reactor was fed with leachate and domestic sewage in ratio of 1:9 by volume respectively, resulting in an AOL of 2.1 kg m-3 d-1. In the second phase of operation the volumetric fraction of leachate was reduced in the proportion of 0.3 to 9.7 of the volume of domestic sewage or 1.6 kg m-3 d-1. The leachate used in this study were from the Metropolitan Landfill in the city of Joao Pessoa and pre-treated for removal of the load of ammonia in piston flow for stripping of ammonia. The domestic wastewater used in this study came from the city where the study was conducted in Campina Grande.In both phases the HRT was 12 hours and the flow of 83L d-1. The influent and effluent of the experimental system were monitored for pH, VFA and TA twice. Analysis of COD, TSS and VSS were monitored weekly. All tests were recommended by APHA (1998). The results show that the combined treatment of landfill leachate diluted domestic sewage in a UASB reactor is technologically feasible alternative and produces effluent with characteristics satisfactory to post-treatment in stabilization ponds. Were obtained removal efficiencies of 44.0, 48.5, 85.4 and 79.9% in the first stage and 59.4, 53.6, 92.7 and 89.8% in the second step for the parameter of COD , STV, TSS and VSS respectively. The second stage had the highest decomposition constants for the parameters of STV, TSS and VSS. It is recommended the continuation of studies of treatment of leachate from landfill diluted sewage with COA than 1.6 kg COD m-3d-1.